2017
DOI: 10.1016/j.msea.2017.01.096
|View full text |Cite
|
Sign up to set email alerts
|

Nanoindentation and wear properties of Ti and Ti-TiB composite materials produced by selective laser melting

Abstract: Ti and Ti-TiB composite materials were produced by selective laser melting (SLM). Ti showed an α΄ microstructure, whereas the Ti-TiB composite revealed a distribution of needle-like TiB particles across an α-Ti matrix. Hardness (H) and reduced elastic modulus (Er) were investigated by nanoindentation using loads of 2, 5 and 10 mN. The results showed higher H and Er values for the Ti-TiB than Ti due to the hardening and stiffening effects of the TiB reinforcements. On increasing the nanoindentation load, H and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(78 citation statements)
references
References 62 publications
5
73
0
Order By: Relevance
“…The wear track of the sample observed by SEM is shown in Figure 7. The wear track of the sample (Figure 7) shows the presence of wear scars along the sliding direction typical for a wear surface and the presence of ploughing grooves and delamination at certain regions similar to that reported in References [39][40][41][42]. The process of coating wear was accompanied by cracking of the coating.…”
Section: Resultssupporting
confidence: 67%
“…The wear track of the sample observed by SEM is shown in Figure 7. The wear track of the sample (Figure 7) shows the presence of wear scars along the sliding direction typical for a wear surface and the presence of ploughing grooves and delamination at certain regions similar to that reported in References [39][40][41][42]. The process of coating wear was accompanied by cracking of the coating.…”
Section: Resultssupporting
confidence: 67%
“…Also, current advances in biotechnology and biomechanics induce the development of new materials and surface treatments that aim to increase wear and corrosion strength, or improve features, which allows the promotion of the biointegration of materials [4][5][6][7][8]. Laser processing techniques imply the ability to perform changes on surface material without direct contact [9][10][11][12][13]. This feature results in a relatively clean and precise process, due to an excellent control over the heat absorption on the affected area, and the possibility of focusing the laser beam on small areas of the surface.…”
Section: Introductionmentioning
confidence: 99%
“…In tribological systems, the harder friction partners reveal less wear as the softer friction partners. This relation between the hardness and the wear resistance in materials has been described in various works [15,16]. Ehtemam-Haghighi et al showed that the wear of the investigated material is related to its ability to resist elastic strain to failure, which is described by the ratio H/E (hardness H to elastic modulus E).…”
Section: Variation Of the Zincdialkyldithiophosphate (Zndtp) Concentrmentioning
confidence: 63%